3 Implementing a home-based cardiac rehabilitation programme for people with heart failure and their caregivers: findings from the SCOT: REACH-HF Study. (21st November 2022) - Taylor, Rod; Purcell, Carrie; Purvis, Anthony; Cleland, John; Cowie, Aynsley; Dalal, Hasnain; Ibbotson, Tracy; Murphy, Clare
Abstract : Background: Despite robust evidence and national guidance recommending cardiac rehabilitation (CR) for heart failure (HF), access remains poor, a situation magnified by COVID-19. The Rehabilitation EnAblement in CHronic Heart Failure (REACH-HF) randomised controlled trial demonstrated the clinical and cost-effectiveness of a novel home-based CR self-management programme. The SCOT:REACH-HF study was designed to provide the understanding of real-world implementation needed for NHS-wide roll-out in a Scottish context. Aim: To 1) compare outcome improvements and delivery costs with those identified in the RCT; and 2) identify facilitators of and barriers to real-world implementation. Methods: A mixed-method implementation study of REACH-HF delivery across six NHS Scotland areas in 2021-22. Health professionals were trained to facilitate delivery of the 12-week programme. We assessed patient- and caregiver-reported outcomes (including health-related quality of life, psychological wellbeing) pre-and post-REACH-HF participation. Primary outcome: Minnesota Living with Heart Failure Questionnaire (MLHF). 136 adults with reduced ejection fraction HF (HFrEF) were recruited, and 101 completed follow-up. 54 participants nominated caregivers, 26 of whom completed follow-up. Qualitative interviews with 20 key health professionals (primarily REACH-HF facilitators) were subject to thematic analysis to explore barriers to and facilitators of implementation. Fidelity, contextual, and economic data were also collected. Results: REACH-HF participation resulted in significant gains in health-related quality of life, as assessed by the MLHF, PROM-CR+, and EQ-5D-5L, and Self-Care of Heart Failure Index (SCHFI). MLHF improvements were both statistically significant and met the minimum clinically important difference in 63% of participants (see figure 1 ). Interviewees were largely positive about REACH-HF – considering it to have 'filled a gap' when no other CR was available – and key issues to support future roll-out were identified. Conclusion: Our findings support the scaled roll-out of REACH-HF. This would offer people with HFrEF, and their families and friends, an accessible alternative to centre-based CR.